Print vs digital : the changing production of Singaporean women's magazines - Cheng, Lydia Rui Jun (Nanyang Technological University, 2020)
Digitalisation has prompted a myriad of changes in the journalism industry. This has affected different aspects of news work, particularly in newsroom production processes. Though such changes have received much scholarly attention, most studies have focused on newspapers and hard news journalism. Much less research has been done on the impact of digitalisation on magazines and lifestyle journalism. Boczkowski (2004, 2005) identified three production factors that are particularly relevant with respect to the adoption of digital technologies in newsrooms: organisational structures, work practices, and representations of users. Through in-depth interviews with 24 journalists from Female, Her World, Harper’s Bazaar Singapore, L’Officiel Singapore, and Elle Singapore and the textual analysis of both the print issues and online websites of these magazines, I looked at how technological advances have affected the three production factors outlined above in Singaporean women’s magazines and the corresponding impact on the content being produced by these publications. The findings suggest that there is a functional differentiation (Hanusch, 2017) in magazine newsrooms, where magazine journalists adopt different values, norms, and behaviours when engaging in print and digital productions. Furthermore, besides production factors, I found that individual-level factors related to magazine journalists’ self-perceptions have also contributed to the functional differentiation in magazine newsrooms. This has resulted in differentiated content and procedures in print and digital productions in Singaporean women’s magazines.